2022
DOI: 10.3389/fmicb.2022.948049
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Novel Microecological Agents and Molasses Role in Digestibility and Fermentation of Rice Straw by Facilitating the Ruminal Microbial Colonization

Abstract: In this study, we evaluated the effect of microecological agents (MA) combined with molasses (M) on the biodegradation of rice straw in the rumen. Rice straw was pretreated in laboratory polyethylene 25 × 35 cm sterile bags with no additive control (Con), MA, and MA + M for 7, 15, 30, and 45 days, and then the efficacy of MA + M pretreatment was evaluated both in vitro and in vivo. The scanning electron microscopy, X-ray diffraction analysis, and Fourier-transform infrared spectroscopy results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Our results showed that YC supplementation could increase the ruminal propionate content through regulating the bacterial composition. In the rumen, the important butyrate-producing bacteria are Butyrivibrio fibrisolvens strains, and the typical characteristic of bacteria belonging to genus Butyrivibrio is to produce butyrate (Ma et al 2022 ). Improvement in Butyrivibrio relative abundance when supplemented with yeast product was reported in previous research (Xiao et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that YC supplementation could increase the ruminal propionate content through regulating the bacterial composition. In the rumen, the important butyrate-producing bacteria are Butyrivibrio fibrisolvens strains, and the typical characteristic of bacteria belonging to genus Butyrivibrio is to produce butyrate (Ma et al 2022 ). Improvement in Butyrivibrio relative abundance when supplemented with yeast product was reported in previous research (Xiao et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 27 ] demonstrated that the abundance of Pseudobutyrivibrio has increased linearly with increasing neutral detergent fiber and acid detergent fiber in the diet of sheep. In addition to Pseudobutyrivibrio , Ma et al [ 28 ] indicated that Succinimonas in the rumen also play a critical role in forage degradation. Conversely, owing to the reduction in the usage of corn straw (containing more xylan, hemicellulose, and fiber) in this study, there were decreases in the abundance of Pseudobutyrivibrio and Succinimonas , suggesting the rumen microflora adapted to the change in dietary ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella species are associated with a plant-rich diet rich in carbohydrates and fiber ( 22 ). Prevotella has the potential to digest and break down complex carbohydrates from food, sugars, and cellulose ( 23 ).…”
Section: Discussionmentioning
confidence: 99%